Opportunities and Challenges of E- Payment System in India - T S, Sujith; C D, Julie (International Journal of Scientific Research and Management (IJSRM), 2017)
Now a day’s world changed to digital world. India tries to stepping towards e-payment system. Electronicpayment system is a payment system through an electronic network. In other words e-payment is a methodin which a person can make Online Payments for his purchase of goods and services without physicaltransfer of cash and cheques, irrespective of location and time. Today India is at a stage of demonetizationso; in the present scenario this study is inevitable to makes electronic payments at any time through theinternet directly to manage the e-business environment. This study aimed to identify the issues andchallenges of electronic payment systems and offer some solutions to improve the e-payment system. Epaymentsystem not only provides more opportunities but many threats also.